Lobby Before the Constitucional Court in Chile, 2006-2020; [Lobby Ante el Tribunal Constitucional en Chile, 2006-2020] - Segovia-Bahamondes, C (Catholic University of Temuco Faculty of Law Economics and Administrative Sciences, 2024)
This paper analyzes the participation of Interest Groups in the cases brought before the Constitutional Court of Chile. Based on the evidence collected in 436 cases followed between 2006 and 2020, we study the general volume of this participation, the areas in which it is developed, and which interests are most represented. It is argued that: a) the participation of IG in the Court s decisions is generally low; b) that the distribution of participation between types of groups is balanced; c) that it concentrates more on matters of civil and political rights, and d) that the interest groups that represent more restricted interests participate more in discussions of an economic nature, and that those that preferentially defend general interests concentrate on civil and political rights processes. Contrasting this evidence with that of the United States, the lobby activity in Chile has a much smaller volume. © 2024, Catholic University of Temuco Faculty of Law Economics and Administrative Sciences. All rights reserved.